Convective System Dynamics Viewed in 3D Over the Oceans. Issue 5 (9th March 2021) - La, Tran Vu; Messager, Christophe
Abstract: Previous studies indicated a relationship between deep convection and sea surface wind patterns; however, it remains difficult to remotely observe a deep Convective System (CS) and its dynamics above the ocean due to the lack of data at the mid atmospheric levels. To collect the details of the CS dynamics, some nearly simultaneous data of three CS features, that is, cloud brightness temperature, vertical wind at the midlevels, and horizontal wind at the sea surface, can be now obtained by a combination of sensors from a geostationary (Meteosat) and two polar‐orbiting satellites (Sentinel‐1 and Aeolus), having corresponding acquisition time and orbit track matching. This work thus illustrates a nearly three‐dimensional view of the CS atmospheric dynamics over the sea, including deep convective clouds observed by Meteosat, intense downdrafts measured by Aeolus, and strong surface winds estimated by Sentinel‐1. Plain Language Summary: Cumulonimbus clouds (anvil‐shaped clouds or convective systems) may be associated with some meteorological hazards, including intense precipitation up to 50 mm/hr, surface wind gust exceeding 25 m/s, and strong lightning. For a long time, the analyses and prediction of cumulonimbus clouds and their effects over the surface have been generally complicated due to the lack of observation data, particularly when cumulonimbus clouds occur suddenly. The understanding and forecast of cumulonimbus have been much improved in recent years thanks to the launch of geostationary satellites (Meteosat, GOES, Himawari, Gaofen) that cover the entire earth with a 5–10 min time sampling. Likewise, surface wind patterns associated with cumulonimbus clouds can be observed by the low altitude polar satellites, especially by the high spatial resolution Sentinel‐1 SAR (Synthetic Aperture Radar) satellite. Furthermore, the launch of the Aeolus satellite on August 22, 2018, enables the observations of the section of vertical wind profiles associated with surface wind gust viewed by Sentinel‐1. The combination of three satellites (Sentinel‐1, Aeolus, and Meteosat) offers an observation of cumulonimbus clouds, their vertical atmospheric movement, and the associated wind gust over the sea surface. The current study indicates that the production of surface wind gust depends on the intensity of the downward air flux from the higher cumulonimbus altitude to the sea surface. Key Points: Midlevel vertical winds essential for 3D observation of convective systems dynamics are available from new Aeolus satellite New methodology combines various satellite observations of brightness temperature, midlevel vertical wind, and surface wind Applying this methodology shows strong relationships between deep convection, downdrafts, and sea surface wind